A prática social do consumo insustentável de alimentos para viagem no Brasil e Alemanha - Coelho, Pedro Felipe da Costa (2021)
This research aimed to understand how the social practice of takeaway food consumption influences the adoption of unsustainable eating practices. To achieve this, the following specific objectives were established: (i) to compare the performances of Brazilian and German consumers who consume takeaway food; (ii) to characterize the social practice of consuming food for travel; (iii) to describe the main environmental and social implications of takeaway food; and (iv) to identify alternatives to reduce the environmental and social cultural implications of takeaway food consumption. The literature review involved takeaway food consumption, sustainable food consumption and food as a social practice. The Theories of Practice was selected as the theoretical and methodological framework of this study. The data were collected through 19 narrative interviews with employees and owners of takeaway food places, 41 in-depth interviews with consumers and 7 months of observations in places of purchase and consumption of meals in Brazil and Germany. For data analysis, the data analysis spiral was used. The results reveal that menus, packaging and disposable objects are the material arrangements that are interdependently related to the meanings and competences of the social practice of takeaway food consumption. Takeaway food is consumed more frequently due to the lack of time and skills to cook, being chosen as an alternative to meals prepared at home or eating out. This social practice that can contribute positively or negatively to the adoption of sustainable eating practices, depending on the menus, the primary and secondary packaging, the portions size and the disposal of the meals. It was possible to identify ten alternatives to mitigate the environmental and social implications of eating takeaway food, which are related to menus, food apps, primary and secondary packaging and skills to cooking. Recommendations are presented to consumers, restaurant entrepreneurs and policy makers.